2012
DOI: 10.1371/journal.pone.0044794
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Consequences of Failure of Linkage to Antiretroviral Therapy at Primary Care Level in Blantyre, Malawi: A Prospective Cohort Study

Abstract: BackgroundPoor rates of linkage from HIV diagnosis to ART initiation are a major barrier to universal coverage of ART in sub-Saharan Africa, with reasons for failure poorly understood. In the first study of this kind at primary care level, we investigated the pathway to care in the Malawian National Programme, one of the strongest in Africa.Methods and FindingsA prospective cohort study was undertaken at two primary care clinics in Blantyre, Malawi. Newly diagnosed HIV-positive adults (>15 years) were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…Patients with underlying multidrug-resistant (MDR) TB treated with first-line therapy were assumed to have worse outcomes. We assumed that 15% of patients testing positive would not complete a sufficient course of therapy to achieve cure 9 . Patients who were false negatives or lost to follow-up had the opportunity of a future TB diagnosis with sputum smear microscopy through the routine health system 8, 10, 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients with underlying multidrug-resistant (MDR) TB treated with first-line therapy were assumed to have worse outcomes. We assumed that 15% of patients testing positive would not complete a sufficient course of therapy to achieve cure 9 . Patients who were false negatives or lost to follow-up had the opportunity of a future TB diagnosis with sputum smear microscopy through the routine health system 8, 10, 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Baseline characteristics of cohort study participants, patterns of HTC and linkage to ART have previously been described [14,15]. …”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that many patients drop out of the programs even before ART initiation with a failure of linkage to ART after HIV testing [47][49].…”
Section: Discussionmentioning
confidence: 99%